Combination of gold catalysis and Selectfluor for the synthesis of fluorinated nitrogen heterocycles - Simonneau, Antoine; Garcia, Pierre; Goddard, Jean-Philippe; Mouriès-Mansuy, Virginie; Malacria, Max; Fensterbank, Louis (Beilstein Journal of Organic Chemistry, 2011)
We herein report the synthesis of 3-fluoro-2-methylene-pyrrolidine (3a) and -piperidine (3b) from 1,5- and 1,6-aminoalkynes, respectively, using a combination of a gold-catalyzed hydroamination reaction followed by electrophilic trapping of an intermediate cyclic enamine by Selectfluor. Careful attention was paid to the elucidation of the mechanism and Selectfluor was suggested to play the double role of promoting the oxidation of gold(I) to a gold(III) active species and also the electrophilic fluorination of the enamine intermediates.
Keywords: cycloisomerization reactions; fluorinated pyrrolidines; gold catalysis; Selectfluor

Modern Fluoroorganic Chemistry - Kirsch, P. (Wiley-VCH, 2004)

Fluorine in Medicinal Chemistry and Chemical Biology - Ojima, I. (Wiley-Blackwell, 2009)

(untitled) - De Haro, T.; Nevado, C. (Adv. Synth. Catal., 2010)

(untitled) - Akana, J. A.; Bhattacharyya, K. X.; Müller, P.; Sadighi, J. P. (J. Am. Chem. Soc., 2007)

(untitled) - Schuler, M.; Silva, F.; Bobbio, C.; Tessier, A.; Gouverneur, V. (Angew. Chem., Int. Ed., 2008)

(untitled) - de Haro, T.; Nevado, C. (Chem. Commun., 2011)

(untitled) - Moreau, X.; Goddard, J.-P.; Bernard, M.; Lemière, G.; López-Romero, J. M.; Mainetti, E.; Marion, N.; Mouriès, V.; Thorimbert, S.; Fensterbank, L.; Malacria, M. (Adv. Synth. Catal., 2008)

(untitled) - Marion, N.; Lemière, G.; Correa, A.; Costabile, C.; Ramón, R. S.; Moreau, X.; de Frémont, P.; Dahmane, R.; Hours, A.; Lesage, D.; Tabet, J.-C.; Goddard, J.-P.; et al. (Chem.–Eur. J., 2009)

(untitled) - Harrak, Y.; Makhlouf, M.; Azzaro, S.; Mainetti, E.; Lopez Romero, J. M.; Cariou, K.; Gandon, V.; Goddard, J.-P.; Malacria, M.; Fensterbank, L. (J. Organomet. Chem., 2011)

(untitled) - Harrak, Y.; Simmonneau, A.; Malacria, M.; Gandon, V.; Fensterbank, L. (Chem. Commun., 2010)

(untitled) - Benedetti, E.; Lemière, G.; Chapellet, L.-L.; Penoni, A.; Palmisano, G.; Malacria, M.; Goddard, J.-P.; Fensterbank, L. (Org. Lett., 2010)

(untitled) - Wang, W.; Jasinski, J.; Hammond, G. B.; Xu, B. (Angew. Chem., Int. Ed., 2010)

(untitled) - Qian, J.; Liu, Y.; Zhu, J.; Jiang, B.; Xu, Z. (Org. Lett., 2011)

(untitled) - Xu, T.; Mu, X.; Peng, H.; Liu, G. (Angew. Chem., Int. Ed., 2011)

(untitled) - Hashmi, A. S. K.; Ramamurthi, T. D.; Rominger, F. (J. Organomet. Chem., 2009)

(untitled) - Engle, K. M.; Mei, T.-S.; Wang, X.; Yu, J.-Q. (Angew. Chem., Int. Ed., 2011)

(untitled) - Hopkinson, M. N.; Gee, A. D.; Gouverneur, V. (Chem.–Eur. J., 2011)

(untitled) - Ney, J. E.; Wolfe, J. P. (Angew. Chem., Int. Ed., 2004)

(untitled) - Hong, S.; Marks, T. J. (Acc. Chem. Res., 2004)

(untitled) - Brenzovich, W. E.; Benitez, D.; Lackner, A. D.; Shunatona, H. P.; Tkatchouk, E.; Goddard, W. A., III; Toste, F. D. (Angew. Chem., Int. Ed., 2010)

(untitled) - Hannedouche, J.; Collin, J.; Trifonov, A.; Schulz, E. (J. Organomet. Chem., 2011)

(untitled) - Trost, B. M.; Maulide, N.; Livingston, R. C. (J. Am. Chem. Soc., 2008)

(untitled) - Rudolph, M.; Hashmi, A. S. K. (Chem. Commun., 2011)

(untitled) - Hirano, K.; Inaba, Y.; Takahashi, N.; Shimano, M.; Oishi, S.; Fujii, N.; Ohno, H. (J. Org. Chem., 2011)

(untitled) - Peng, H.; Liu, G. (Org. Lett., 2011)

(untitled) - Yeom, H.-S.; So, E.; Shin, S. (Chem.–Eur. J., 2011)

(untitled) - Mankad, N. P.; Toste, F. D. (J. Am. Chem. Soc., 2010)

(untitled) - Peng, W.; Shreeve, J. M. (J. Org. Chem., 2005)

(untitled) - Schomaker, J. M.; Geiser, A. R.; Huang, R.; Borhan, B. (J. Am. Chem. Soc., 2007)

(untitled) - Garcia, P.; Evanno, Y.; George, P.; Sevrin, M.; Ricci, G.; Malacria, M.; Aubert, C.; Gandon, V. (Org. Lett., 2011)

(untitled) - Fix, S. R.; Brice, J. L.; Stahl, S. S. (Angew. Chem., Int. Ed., 2002)